The cyclic nucleotide cGMP is involved in plant hormone signalling and alters phosphorylation of Arabidopsis thaliana root proteins - Isner, Jean Charles; Nühse, Thomas; Maathuis, Frans J. M. (Journal of experimental botany, 2012)
The cyclic nucleotide cGMP has been shown to play important roles in plant development and responses to abiotic and biotic stress. Yet much controversy remains regarding the exact role of this second messenger. Progress in unravelling cGMP function in plants was hampered by laborious and time-consuming methodology to measure changes in cellular [cGMP] but the development of fluorescence-based reporters has removed this disadvantage. This study used the FlincG cGMP reporter to investigate potential interactions between phytohormone and cGMP signalling and found a rapid and significant effect of the hormones abscisic acid (ABA), auxin (IAA), and jasmonic acid (JA) on cytoplasmic cGMP levels. In contrast, brassinosteroids and cytokinin did not evoke a cGMP signal. The effects of ABA, IAA, and JA were apparent at external concentrations in the nanomolar range with EC50 values of around 1000, 300, and 0.03 nmoles for ABA, IAA, and JA respectively. To examine potential mechanisms for how hormone-induced cGMP signals are propagated, the role of protein phosphorylation was tested. A phosphoproteomics analysis on Arabidopsis thaliana root microsomal proteins in the absence and presence of membrane-permeable cGMP showed 15 proteins that rapidly (within minutes) changed in phosphorylation status. Out of these, nine were previously shown to also alter phosphorylation status in response to plant hormones, pointing to protein phosphorylation as a target for hormone-induced cGMP signalling.